2013
DOI: 10.1186/2193-1801-2-672
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiologic characteristics of non Hodgkin’s lymphoma in Bedouins in the south of Israel

Abstract: The presentation of Non Hodgkin’s Lymphoma (NHL) may vary in relation to ethnicity or environmental effects. The objective of our study was to characterize NHL among the Negev Bedouin population, compared to the Jewish population.Retrospective data were collected for 45 Bedouin and 45 Jewish patients who were treated at Soroka University Medical Center between 1990 and 2007.Upon diagnosis, rates of aggressive NHL types, involvement of extra-lymphatic organs, as well as mean LDH were higher among Bedouin. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…The difference in outcome of hematological malignancies was demonstrated in adult patients belonging to the Bedouin population . Levi et al demonstrated higher rates of aggressive non‐Hodgkin lymphoma, involvement of extralymphatic organs, as well as mean LDH among adult Bedouins compared with Jews, together with poorer OS and disease free survival (DFS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference in outcome of hematological malignancies was demonstrated in adult patients belonging to the Bedouin population . Levi et al demonstrated higher rates of aggressive non‐Hodgkin lymphoma, involvement of extralymphatic organs, as well as mean LDH among adult Bedouins compared with Jews, together with poorer OS and disease free survival (DFS).…”
Section: Discussionmentioning
confidence: 99%
“…The difference in outcome of hematological malignancies was demonstrated in adult patients belonging to the Bedouin population . Levi et al demonstrated higher rates of aggressive non‐Hodgkin lymphoma, involvement of extralymphatic organs, as well as mean LDH among adult Bedouins compared with Jews, together with poorer OS and disease free survival (DFS). Levy et al demonstrated the Bedouins suffering from Hodgkin lymphoma had higher incidence of mixed cellularity histology, more advanced disease at diagnosis, higher rates of resistant disease (8.7‐fold), and lower OS and DFS compared with other populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was done in patients with Iranian ethnicity that Wang (2008) documented the impact of racial and ethnic disparities in access to treatment for DLBCL that could increase disparities in outcomes such as survival in the presence of R-CHOP. Also, Levi (2013) reported that affecting of treatment in NHL patients may be different in ethnic groups.…”
Section: Discussionmentioning
confidence: 99%